I dati metereologici per applicazioni energetiche e ambientali - Mandurino, Claudia <1975> (Alma Mater Studiorum - Università di Bologna, 2009)
Many energetic and environmental evaluations need appropriate meteorological data, as input to analysis and prevision softwares. In Italy there aren't adeguate meteorological data because, in many cases, they are incomplete, incorrect and also very expensive for a long-term analysis (that needs multi-year data sets).